Annalysis of Epidemiological Surveillance Activity of the COVID-19 at Surabaya Airport Indonesia on January 2020 - Nastiti, Rizma Dwi; Artanti, Kurnia Dwi; Faqih, Achmad Faridy (UI Scholars Hub, 2020)
The Surabaya Port Health Office (PHO) Class I is tasked with the disease prevention by detection, response and protection at entrance gates for the sea and airports and over the state cross-border posts regarding the situation of COVID-19 pandemic. This analysis aimed to assess activities of early warning alert and response system to COVID-19 at Juanda International Airport on January 2020. The method used includes interviewing four informants, studying of docu - ments and directing field-observation by following activities of PHO, who supervise, inspect General Declarations, distribute, and collect the Health Alert Card (HAC) and monitor body temperature of travelers. The analysis uses a system approach and 4M model with modification by adding time, technology and information variables. Activities in the early warning alert and response system of COVID-19 are in accordance with the Preparedness Guidelines by the Indonesian Goverment. The outputs of reported activities have been classified as appropriate. The HAC form is lacking as a source of COVID-19 surveillance, address information part is often being misinterpreted by travelers. It is necessary to add additional questions regarding the destination address of travelers, and to educate on how to fill HAC correctly so that the effectiveness of HAC can be maximized.